Pre-Mesozoic Geology of Iberia - Dallmeyer, R. David; Garcia, Enrique Martinez (IGCP-Project 233, Terranes in the Circum-Atlantic Paleozoic Orogens, 1990)
Pre-Mesozoic Geology of Iberia is a major reference for current understanding of the overall tectonostratigraphic evolution of the Iberian Massif. It represents a comprehensive overview which systematically describes characteristics of the seven major lithotectonic elements of the Iberian Massif in terms of: - stratigraphy, - paleontology, - sedimentology, - structural geology, - igneous activity, - metamorphic evolution, - metallogenesis, and - tectonic significance. These data are compiled in several concluding summary chapters which discuss the overall geodynamic evolution of the Iberian Massif and outline its tectonic setting within the overall circum-Atlantic region. Readers will benefit by this comprehensive review of an important tectonostratigraphic element in the circum-Atlantic realm